2013
DOI: 10.1103/physrevb.87.125308
|View full text |Cite
|
Sign up to set email alerts
|

Dangling-bond defect in a-Si:H: Characterization of network and strain effects by first-principles calculation of the EPR parameters

Abstract: The performance of hydrogenated amorphous silicon (a-Si:H) solar cells is severely affected by the light-induced formation of metastable defects in the material (Staebler-Wronski effect). The common notion is that the dangling-bond (db) defect, a three-fold coordinated silicon atom, plays a key role in the underlying mechanisms. To support the characterization of this defect by electron paramagnetic resonance (EPR), we present in this work a first-principles study of the EPR-parameters for a structural ensembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…These trends are easily understood: decreasing the hydrogen in the structure limits the number of bonds needed to be satisfied, and thus decreases the propensity toward FB creation in the structure, while compressing the material decreases bond distances, making FBs more likely. DBs were observed to universally contribute less substantially to the band tails within the studied ensembles, in agreement with previous results [13,22].…”
Section: Moving From 10% [H] To 5% [H] (Solid To Dashed Curves)supporting
confidence: 92%
See 1 more Smart Citation
“…These trends are easily understood: decreasing the hydrogen in the structure limits the number of bonds needed to be satisfied, and thus decreases the propensity toward FB creation in the structure, while compressing the material decreases bond distances, making FBs more likely. DBs were observed to universally contribute less substantially to the band tails within the studied ensembles, in agreement with previous results [13,22].…”
Section: Moving From 10% [H] To 5% [H] (Solid To Dashed Curves)supporting
confidence: 92%
“…Additional works have experimentally measured hole mobilities in deposited films over ranges of deposition conditions [14][15][16], and modeled the densities of band-tail states implied from these measurements [17][18][19][20][21]. Studies have also sought to measure densities of coordination defects experimentally, namely through electron paramagnetic resonance (EPR), although recent work has shown that such results are challenging to interpret because of the importance of the surrounding geometry on the measurement of the coordination defect [22]. However, despite this abundance of work, a detailed understanding of the atomic structure of hole trapping mechanisms over a range of experimental deposition conditions (necessary to satisfactorily sample the large configuration space possible for a-Si:H) is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A similar theory has been put forth by Morigaki [45], in which the Si-H-Si structures are described as hydrogen-related dangling bonds in which the hydrogen atom is preferentially bound to one silicon atom. This model has been challenged by electron-spin-resonance studies indicating that there are no hydrogen atoms within 3Å of dangling bonds in a-Si:H [46,47], but more recent studies have called this conclusion into question [48][49][50]. About 2% of the structures in our sample, and three of the eight deepest hole traps, contain bridge bonds in which the difference between the two H-Si bond lengths is less than 0.05Å.…”
Section: Ds Dmentioning
confidence: 76%
“…Various researchers have been investigated the reduction reaction of oxygenated functional groups by H-terminated silicon surface 73 74 75 76 . The reduction reactions have been conducted by Si-H dangling bonds 77 78 79 , which were formed during etch process as shown in figure S8 80 81 82 83 . The fluoride ion of remaining very small amount of HF on silicon surface after the etching process, also could help to activate these Si-H bonds 73 .…”
Section: Discussionmentioning
confidence: 99%